Improving IV-Cath Insertion Knowledge Using Comics for Nursing Students at the Health Polytechnic of Palembang in Baturaja - Wijaya, Sapondra; Ulfa, Msy Hartina; Wibowo, Wahyu Dwi Ari; Rohana, I Gusti Ayu Putu Desy (Alta Dharma Publisher, 2023)
Introduction: One of the most critical aspects that determine the growth of education is learning, which is a process of obtaining a lot of development, both in terms of knowledge, attitudes, and skills. One thing that needs to be improved is the knowledge and skills of IV-Cath insertion as a basis for nursing practice. One of the educational media to attract students' attention is comics. The advantage of the comic is that it is easy to understand with simple pictures plus words in daily language so that comics can be read easily. Objective: The study aimed to test the effect of the IV-Cath Comic on knowledge of IV-Cath Insertion in nursing students Baturaja, South Sumatra, Indonesia. Method: This research was a quantitative study with a quasi-experimental approach using pre and post-tests with a total sample of 78 nursing students from the Health Polytechnic of Palembang in Baturaja. Data analysis used the Wilcoxon test because the data was not normally distributed. Result: The results of the Wilcoxon analysis test obtained the value of Sig. (2-tailed) of 0.000 <0.05, an average difference exists between the pre-and post-test scores. Conclusion: In conclusion, there is an increase in knowledge of IV-Cath insertion after using comic media. Recommendation: This IV-Cath comic can be used as a practical learning media to increase students' knowledge about IV-Cath insertion. For further research, we suggest examining student motivation and enthusiasm for learning.